1993
DOI: 10.1093/bja/70.6.666
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Ketamine Enantiomers in Surgical Patients Using a Stereoselective Analytical Method

Abstract: In a randomized, double-blind study, we have examined the stereoselective disposition and pharmacodynamic characteristics of ketamine in surgical patients after i.v. administration of S(+)-ketamine 1 mg/kg body weight (25 patients) or racemic ketamine 2 mg/kg body weight (25 patients). S(+)-Ketamine was not inverted to R(-)-ketamine. After racemate administration we observed statistically significant (P < 0.01) smaller clearance and volume of distribution for R(-)-ketamine compared with S(+)-ketamine. In contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(42 citation statements)
references
References 20 publications
5
32
0
Order By: Relevance
“…The relative plasma concentrations of (R)-/(S)-Ket and (R)-/(S)-norKet were 1.3 and 1.4, respectively, Fig 2B, which is consistent with data from the previous study where the average (R)-/(S)-Ket and (R)-/(S)-norKet plasma concentrations were 1.1 and 1.2, respectively [1,2]. The relative concentrations reflect the previous reports that there is a significant difference in the plasma clearance of (R)-Ket versus (S)-Ket and that the C max and AUC values for (R)-norKet are greater than those of (S)-norKet [1,2,6,7,10]. The relative plasma concentration of (R)-/(S)-DHNK was 1.4, which represents the first report of the relative enantiomeric plasma concentrations of these compounds in humans after the administration of (R,S)-Ket.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…The relative plasma concentrations of (R)-/(S)-Ket and (R)-/(S)-norKet were 1.3 and 1.4, respectively, Fig 2B, which is consistent with data from the previous study where the average (R)-/(S)-Ket and (R)-/(S)-norKet plasma concentrations were 1.1 and 1.2, respectively [1,2]. The relative concentrations reflect the previous reports that there is a significant difference in the plasma clearance of (R)-Ket versus (S)-Ket and that the C max and AUC values for (R)-norKet are greater than those of (S)-norKet [1,2,6,7,10]. The relative plasma concentration of (R)-/(S)-DHNK was 1.4, which represents the first report of the relative enantiomeric plasma concentrations of these compounds in humans after the administration of (R,S)-Ket.…”
Section: Resultssupporting
confidence: 79%
“…3B. Since previous studies demonstrated that norKet is hydroxylated at the C4, C5 and C6 positions on the cyclohexanone ring [6,7], the four unknown compounds were identified as HNK metabolites and labeled as compounds 4c, 4d, 4e and 4f . While the structures of 4c – 4f have not been definitively identified, it is possible to make tentative assignments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our current study, we observed that 0.1–0.3 mM ketamine did not induce complete anesthesia in the embryos and these doses did not alter DA levels. In patients, ketamine plasma sub-anesthetic concentrations range from 0.5–1 µM and anesthesia sets in at ~10–100 µM range (Domino et al, 1982; Geisslinger et al, 1993; Idvall et al, 1979). Our studies on zebrafish embryos treated with 2 mM ketamine that were completely anesthetized (Cuevas et al, 2013) show an internal exposure of ~8 µM (Trickler et al, 2014) and is comparable to the human anesthetic dose range.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Equipotent doses of the S(+)-isomer and the racemate appear to have similar effects on physiologic parameters. [8] There is evidence to suggest that the R(-)-isomer produces a higher rate of emergence reactions and more agitated behavior than the S(+) isomer. [9]…”
Section: Resultsmentioning
confidence: 99%